Timber frame dwellings : U-values and building regulations - Doran, S. M. (BRE special digest, 2002)
This digest explains how the requirements of the Building Regulations for Conservation of Fuel and Power may be satisfied for a dwelling built with timber frame construction. For dwellings, a choice of three routes to compliance is available: the element method, the target u-value method, and the carbon index method. This digest describes these methods and gives examples of how they can be applied.